I have to evaluate the series: $$\sum_{k=1}^\infty \left(\frac{1}{36k^2-1}+\frac{2}{(36k^2-1)^2}\right).$$

I tried using the identity $\sum_{k=1}^{\infty}\frac{1}{k^2}=\frac{\pi^2}{6}$ but I got stuck.

  • $\begingroup$ Did you try partial fractions? $\endgroup$ – abiessu Mar 2 '16 at 16:08
  • 1
    $\begingroup$ Hint: $36k^2-1=(6k+1)(6k-1)$ $\endgroup$ – Nikunj Mar 2 '16 at 16:08
  • $\begingroup$ @Nikunj The sequence in the problem converges to an irrational number, notably $\frac{\pi^2-9}{18}$. So partial fractions are unlikely to help very much, I think. $\endgroup$ – S.C.B. Mar 2 '16 at 16:10
  • $\begingroup$ $\frac{1}{36k^2-1}=\frac{1}{2}\frac{(6k+1)-(6k-1)}{(6k+1)(6k-1)}$ $\endgroup$ – Nikunj Mar 2 '16 at 16:12
  • 1
    $\begingroup$ Write $$1=\dfrac{6k+1-(6k-1)}2$$ and $$2=\dfrac{\{6k+1-(6k-1)\}^2}2$$ $\endgroup$ – lab bhattacharjee Mar 2 '16 at 16:24

A more general approach, proving the identity: $$ \sum_{k\geq 1}\frac{k^2+x^2}{(k^2-x^2)^2}=-\frac{1}{2x^2}+\frac{\pi^2}{2\sin^2(\pi x)}\tag{1}$$ for any $x\in(-1,1)$ is to check that both the LHS and the RHS of $(1)$ are meromorphic functions with the same-behaving singularities at any $x\in\mathbb{Z}\setminus\{0\}$. For instance, $(1)$ is just a consequence of: $$ \sum_{n\in\mathbb{Z}}\frac{1}{(z-n)^2}=\frac{\pi^2}{\sin^2(\pi z)}\tag{2} $$ since $\frac{1}{(k-x)^2}+\frac{1}{(k+x)^2} = 2\cdot\frac{k^2+x^2}{(k^2-x^2)^2}$. $(2)$ can be seen as a consequence of the reflection formula for the $\Gamma$ function, too, since: $$ \sum_{n\in\mathbb{Z}}\frac{1}{(z-n)^2}= \psi'(-z)+\psi'(1+z). \tag{3}$$ If we plug $x=\frac{1}{6}$ in $(1)$, we get:

$$ \sum_{k\geq 1}\frac{36k^2+1}{(36k^2-1)^2} = \color{red}{\frac{\pi^2-9}{18}}\tag{4} $$

and it is possible to derive such identity also through Fourier-analytic methods.

Still another way is to notice that our series is just $\frac{1}{2}\cdot L(\chi,2)$ where $\chi$ is the principal Dirichlet character $\!\!\pmod{6}$, hence our series depends on $\text{Li}_2$ evaluated at the sixth roots of unity.

An elementary proof of $(4)$ comes from the inclusion-exclusion principle: $$ \sum_{k\geq 0}\left(\frac{1}{(6k+1)^2}+\frac{1}{(6k+5)^2}\right) = \sum_{\substack{n\geq 1 \\ 2\nmid n \\ 3\nmid n}}\frac{1}{n^2} = \sum_{n\geq 1}\frac{1}{n^2}-\sum_{\substack{n\geq 1 \\ 2\mid n}}\frac{1}{n^2}-\sum_{\substack{n\geq 1 \\ 3\mid n}}\frac{1}{n^2}+\sum_{\substack{n\geq 1 \\ 6\mid n}}\frac{1}{n^2}$$ gives:

$$ \sum_{k\geq 0}\left(\frac{1}{(6k+1)^2}+\frac{1}{(6k+5)^2}\right) = \left(1-\frac{1}{4}-\frac{1}{9}+\frac{1}{36}\right) = \frac{2}{3}\cdot\zeta(2) = \color{red}{\frac{\pi^2}{9}}. \tag{5}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.